The voice of the puppet (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
The puppet as performing object invites vocalization that is different from the normal human voice. Choices to suit body size, stylized features, and the animated objects tendency toward extra-daily sound—song and music—reinforce the otherness of the performing object. Three major types of vocal concepts are presented: 1) the one person, many voices show, which can use different resonators, pitches, and speeds as exemplified in the wayang golek of West Java; 2) the two-voice show, where the puppeteer may speak with a voice modifier such as a swazzle and the dialogue interpreted by a more normative human voice, in traditional puppetry it will often be a musician or interlocutor/back chat who sits outside the booth; and 3) the multi-voice show where individual speakers are often used for each figure, while dialogue may pre-recorded, delivered from the side by appropriate voice actors, or by each of the individual manipulators who speak for their own figure.Keywords: Voice. Puppet. Swazzle. Wayang Golek. Backchat.